MODELLING 2-D PONDASI JEMBATAN BERDASARKAN PEMBEBANAN DAN LETAK POSISI BATUAN ‘X’ - Risal Ardiansyah Putra; Fachri Almawali A F; Widya Utama (Prokons: Jurnal Teknik Sipil, 2020)
This paper contains an analysis of the loading and the position of rock in the bridge foundation based on the rock's response to the force that will be tested with "Graphic User Interface (GUI)" program using MATLAB. This paper also explains the preparation of bridge foundation modeling based on the forces tested on the rock named ‘x’. The response forces discussed in this paper are normal force, latitude force and moment force.                 The data is processed using MATLAB software and then presented in the form of tables, graphs and 2D modeling that shows the loading and the position of rocks correspondence to the bridge foundation. After obtaining the rock’s ‘x’ data, the data is then processed using Graphic User Interface program, through the program moment force graphs, normal force graphs, latitude graphs can be obtained which later these results can be considered for modeling the loading and the position of the rock’s ‘x’.                 Through the data processing that has been done, zero normal force is obtained, and the latitude has a value of about (0 to 8) N and the moment force of about (-60 to 0) N. Based on these calculations it was found that the rock’s 'x' can be modeled by arranging it rectangle with center of gravity evenly distributed at the center. And the model that are used is the placement pinch model because it does not have translational and rotational values so that the rock ‘x’ is suitable to be the bridge's foundation.Keywords: Shear forces, Bending Moment, Normal Forces, GUI, Modelling